Extracellular DNA—A Danger Signal Triggering Immunothrombosis - Shi, Chongxu; Yang, Luying; Braun, Attila; Anders, Hans-Joachim (Frontiers in Immunology, 2020)
Clotting and inflammation are effective danger response patterns positively selected by evolution to limit fatal bleeding and pathogen invasion upon traumatic injuries. As a trade-off, thrombotic and thromboembolic events complicate severe forms of infectious and non-infectious states of acute and chronic inflammation, i.e. immunothrombosis. Factors linked to thrombosis and inflammation include mediators released by platelet granules, complement and lipid mediators, and certain integrins. Extracellular deoxyribonucleic acid (DNA) was a previously unrecognized cellular component in the blood, which elicit profound proinflammatory and prothrombotic effects. Pathogens trigger the release of extracellular DNA together with other pathogen-associated molecular patterns. Dying cells in the inflamed or infected tissue release extracellular DNA together with other danger-associated molecular patterns (DAMPs). Neutrophils release DNA by forming neutrophil extracellular traps (NETs) during infection, trauma, or other forms of vascular injury. Fluorescence tissue imaging localized extracellular DNA to sites of injury and to intravascular thrombi. Functional studies using deoxyribonuclease (DNase)-deficient mouse strains or recombinant DNase show that extracellular DNA contributes to the process of immunothrombosis. Here, we review the evolving evidence for extracellular DNA as a driver of immunothrombosis and discuss challenges and prospects for extracellular DNA as a potential therapeutic target.